2000
DOI: 10.1007/s002050000088
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Thin Films of Martensitic Materials

Abstract: We study the effective behavior of heterogeneous thin films with three competing length scales: the film thickness and the length scales of heterogeneity and material microstructure. We start with three-dimensional nonhomogeneous nonlinear elasticity enhanced with an interfacial energy of the van der Waals type, and derive the effective energy density as all length scales tend to zero with given limiting ratios. We do not require any a priori selection of asymptotic expansion or ansatz in deriving our results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 32 publications
(59 reference statements)
4
44
0
Order By: Relevance
“…About one year later, Shu [21] has shown that letting the interfacial energy go to zero the variational limit coincides with that obtained by Le Dret and Raoult. Bělík and Luskin [6] have observed that with the energy considered by Bhattacharya and James [8] the deformations with finite energy cannot have sharp interfaces between compatible variants.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…About one year later, Shu [21] has shown that letting the interfacial energy go to zero the variational limit coincides with that obtained by Le Dret and Raoult. Bělík and Luskin [6] have observed that with the energy considered by Bhattacharya and James [8] the deformations with finite energy cannot have sharp interfaces between compatible variants.…”
Section: Introductionsupporting
confidence: 75%
“…About one year later Shu [21] has shown that if ε and κ(ε) go to 0 then the total energy considered by Bhattacharya and James Γ -converges, in a suitable topology, to the one obtained by Le Dret and Raoult.…”
Section: Previous Results and Some Remarksmentioning
confidence: 92%
“…Theorem 2 has interesting consequences for the scaling of the energy in thin martensitic films [3,20] which will be discussed in a forthcoming paper.…”
Section: There Exists a Positive Constant C(ω H) With The Followinmentioning
confidence: 98%
“…We can show that if κ d, it costs materials more energy to form microstructure inside each grain and consequently strains can not be recovered unless the texture is exceptional. Our result 21) shows that the effective behavior of the film is obtained by averaging the properties of small grains, then passing to the two-dimensional limit. Finally, the analysis on the case of comparable κ and d is difficult but it interpolates the two extreme cases.…”
Section: Extremely Small Grainsmentioning
confidence: 68%
“…Thus, one can find an effective theory for this heterogeneous film in the limit when all length scales tend to zero, but with possibly different limiting ratios. Shu 21) has used the framework of Γ -convergence to show that the average behavior of the film is determined by an effective two-dimensional theory. The limiting theory implies that the overall deformation y has three components y 1 , y 2 and y 3 which depend only on the in-plane variable x 1 and x 2 .…”
Section: Theorymentioning
confidence: 99%